1997
DOI: 10.1109/20.559969
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of solid propellant combustion behavior under electrothermal plasma injection for ETC launchers

Abstract: A b s t r a c t -E n h a n c e d burn rates o f s o l i d

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…In this study, a discharge current profile, Fig. 2, was taken from one of the experiments on the PIPE facility at NC State University as a model for the discharge current in Lexan capillaries [3], [11]. The 130µs discharge current peaks to 28.875kA in 30µs and it has been used in all computational simulation in this research.…”
Section: Tapered Electrothermal Capillary Conceptmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, a discharge current profile, Fig. 2, was taken from one of the experiments on the PIPE facility at NC State University as a model for the discharge current in Lexan capillaries [3], [11]. The 130µs discharge current peaks to 28.875kA in 30µs and it has been used in all computational simulation in this research.…”
Section: Tapered Electrothermal Capillary Conceptmentioning
confidence: 99%
“…Electrothermal capillary plasma sources in the ETC guns were utilized as an igniter to the bulk-loaded propellant and as an augmentation mechanism to the burn rates of solid propellant [8]- [11]. The importance of ETC research is in its ability to launch projectiles at very high velocities in excess of 5-7km/s, which can't be achieved by conventional gun systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the heat transfer mechanism from plasmas is by a process of radiative heat transfer (9 -12) with plasma temperatures being quoted as around 10 000 K -30 000 K. The presence of a vapour shield (10,13) preventing excessive radiation from plasmas reaching solid surfaces suggests that the transfer mechanism for ignition to solid propellants may be other than radiative. However, radiation is still thought to have an important role not only in ignition but also in the initiation, control and optimisation of all plasma=propellant interaction processes (12,14,15) .…”
Section: Plasma Heat Transfer Coefficients -Radiationmentioning
confidence: 99%
“…ET capillary plasma sources in the ETC guns were utilized as an igniter to the bulk-loaded propellant and as an augmentation mechanism to the burn rates of solid propellant [8]- [11]. The importance of ETC research is in its ability to launch projectiles at very high velocities in excess of 5-7 km/s, which cannot be achieved by conventional gun systems.…”
Section: Introductionmentioning
confidence: 99%